APAKAH FITUR SHOPEE LIVE, RELIGIUSITAS, DAN GAYA HIDUP MEMPENGARUHI PERILAKU KONSUMSI ISLAM? - Fayi Azzahra, Almirah; Canggih, Clarashinta (Universitas Negeri Surabaya, 2024)
Shopping that previously required consumers to come directly to the shopping place, can now be done by shopping online via the live streaming feature. The aim of this research is to analyze the influence of the Shopee Live feature, religiosity and lifestyle on the Islamic consumption behavior of the people of the city of Surabaya. The research method uses quantitative methods with primary data sources obtained from distributing questionnaires online. Sampling used purposive sampling technique with a total of 125 respondents. The technique used in data analysis is structural equation modeling- partial least squares (SEM-PLS) in SmartPLS 4 software. The results of the research show that there is a significant influence on the Shopee Live feature and religiosity on Islamic consumption behavior, while lifestyle has no effect on behavior. Islamic consumption. This shows that the promotion on Shopee Live does not make people shop because they want to and continue to behave in Islamic consumption.